Řečová integrace příslušníků minorit - Rangelova, Albena; Janovec, Ladislav (Lidé města, 2006)
Presented contribution was created based on texts collected within the project titled Language integration of foreigners in the area of vocabulary undertaken in the Czech Language Institute of Academy of Sciences of the Czech Republic, in the period between 2001-2003. We trace spoken texts of members of immigrant minorities, namely Bulgarian, Ukrainian, and Russian. When this material was collected, there was certain unbalance of the sample regarding number of respondents of different nationalities (the largest sample was Bulgarian, the smallest was Russian). Despite this shortcoming, the texts allowed the most general comparison of types of relevant interference effects related to membership of individual Slavonic nations (or languages): Thus we traced classes of mistakes connected with certain language effect that differs in the native and learned language. It must be also stressed that quantitative research in this area is very demanding: Examined minority communities, defined by their language only, are socially very diverse and thus we limited ourselves to just probe the qualitative analysis of this topic. We tried to understand and appropriately interpret connections and relations of language behavior of a foreigner in contact with majority society using its (majority) language.